2015
DOI: 10.1080/00036846.2015.1117048
|View full text |Cite
|
Sign up to set email alerts
|

The public sector and convergence with spatial interdependence: empirical evidence from Spain

Abstract: https://repositorio.uam.es Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
5
4
0
Order By: Relevance
“…For the period analyzed, an insignificant influence of public investment and education on the growth rate of the European countries is derived from the estimation carried out. These results are consistent with the findings of many researchers (Bartkowskaa and Riedl, 2012;Alvarez and Barbero, 2016). But the overall valuation of the studies is mixed.…”
Section: Data and Resultssupporting
confidence: 90%
“…For the period analyzed, an insignificant influence of public investment and education on the growth rate of the European countries is derived from the estimation carried out. These results are consistent with the findings of many researchers (Bartkowskaa and Riedl, 2012;Alvarez and Barbero, 2016). But the overall valuation of the studies is mixed.…”
Section: Data and Resultssupporting
confidence: 90%
“…In other words, positive spatial spillover occurs. This finding supports the result of Aspiansyah & Damayanti (2019), Álvarez &Barbero (2016), andSun et al (2017). Hence, when a region neighbors another richer region, the former region will benefit from the latter region's economic activity due to intensive commercial relations between the two (Álvarez & Barbero, 2016).…”
Section: Panel Data Of Spatial Econometric Model (Spatial Durbin Model)supporting
confidence: 85%
“…If the result is not equal to 0, fixed effect model must be used. However, various similar previous studies by Sun et al (2017) 2017), dan Álvarez & Barbero (2016) found that, should the research on regional economic growth be conducted using MRW Model, the most theoretically appropriate regression type is the Spatial Durbin Model. This model enables the determination of a region's economic growth with the help of the region's independent variables, other region's economic growth, and independent variables of other regions (Aspiansyah & Damayanti, 2019).…”
Section: Panel Data Spatial Econometric Model (Spatial Durbin Model)mentioning
confidence: 86%
“…The literature on spatial patterns in local taxes provides evidence of tax mimicking among municipalities (Allers & Elhorst, 2005;Cassette, Di Porto & Foremny, 2012;Delgado & Mayor, 2011). The work of Álvarez and Barbero (2016) highlights the importance of spatial effects of tax income on growth in Spanish regional economies, analysing at the same time competition among regions for public resources.…”
Section: Spatial Effects In the Financial Situation Of Territorial Aumentioning
confidence: 99%